Relasi Prasangka dan Doa Perspektif Sayyid Quṭub Dalam Tafsir Fī Ẓilālil Qur’ān - Eko Fajar Susanto; Egi Sukma Baihaki (At-Tafasir: Journal of Al-Qur'an Studies and Contextual Tafsir, 2025)
This research is in-depth into the problem of the relationship between prejudice and prayer, which can cause prayers not to be answered or cause someone to give up praying. This research aims to explain in detail the relationship between prejudice and prayer in Sayyid Quṭb's view in the book Tafsir Fī Ẓilāl Al-Qur’ān. This research uses a textualist approach which will require research to focus on the Tafsir Fī Ẓilāl Al-Qur’ān text by Sayyid Quṭb as the main source of analysis. The research method used is qualitative, which aims to explain in detail the relationship between prejudice and prayer in Sayyid Quṭb's view. The result of this research is that Sayyid Quṭb emphasized that worship to Allah SWT. will be accepted if it is accompanied by good prejudice (ḥusnuẓann). In contrast, bad prejudice (Sū’ al-ẓann) can make the prayer unacceptable to Him.